Liquidity shocks and SEO underpricing - Dai, Kai (2012)
We hypothesise that certain market conditions could lead to liquidity shocks that will consequently increase SEO underpricing (defined as the close-to-offer return). We propose three scenarios of market conditions, namely aggregate issues with large volume, large market declines and market volatility. Using a sample of about 5,000 seasoned equity offerings from 1987 to 2009, we found that market volatility is significantly and positively related to SEO underpricing after controlling for other factors.